Silver effect on water purification and sterilization - Lec. Iman Jaber Hasen (University of Thi-Qar Journal, 2021)
Colloidal Silver Filters are simple devices used for home water treatment on the basis of physical treatment that do not require power supply. Colloidal Silver Filters utilization a vessel, mud candle, or nipping made of pored ceramic material like to conventional ceramic nominee. However in colloidally silver candidate , colloidal silver is use to promote the hindering microorganism, bacteria and another types of microbes. The filter assembly contained two vessel : the upper vessel carry the ceramic plated with colloidally silver , filters the water , and murder the bacteria and the microorganism, and the lower vessel saves treated water. Colloidal silver filters removes turbidity and pathogens from drinking water. Colloidal silver candidate can be built with locally prepared materials , that can contribute to expanding of local trade.